Artificial Intelligence in crisis management - Stranjik, Alen; Kozlevac, Dino; Turčić, Ivica (Crisis Management Days, 2024)
Artificial Intelligence (AI) plays a crucial role in crisis management by enhancing response capabilities, decision-making processes, and resource allocation during emergencies. AI technologies like machine learning, natural language processing, and predictive analytics are utilized to analyse vast amounts of data, identify patterns, and provide valuable insights to emergency responders and decision-makers. AI-powered systems can help in early detection of crises, real-time monitoring of situations, optimizing resource deployment, and even predicting future crisis scenarios based on historical data. By leveraging AI in crisis management, organizations and governments can improve response times, enhance situational awareness, and ultimately save lives and minimize the impact of disasters on communities. In crisis management, AI is used for various purposes: Early Warning Systems: AI can analyse data from various sources like social media, sensors, and satellite imagery to detect early signs of potential crises such as natural disasters or disease outbreaks. Resource Optimization: AI algorithms can optimize the allocation of resources like personnel, equipment, and supplies based on real-time data and predictive models to ensure efficient response to crises. Decision Support: AI systems provide decision-makers with data-driven insights and scenario analysis to make informed decisions quickly during emergencies. Communication and Information Management: AI-powered chatbots and natural language processing tools can streamline communication with the public, provide real-time updates, and gather information from affected populations. Predictive Analytics: AI can forecast the impact of crises, model different scenarios, and help in developing proactive strategies to mitigate risks and reduce the severity of disasters. However, the key challenges of implementing AI in crisis management include data availability and quality, ethical considerations, limited resources and collaboration, complexity of crisis scenarios, organizational and cultural barriers, and the need for robust regulatory and governance frameworks. Data Availability and Quality: The effectiveness of AI-based crisis management solutions depends on the availability and quality of data. Challenges include obtaining comprehensive, real-time data from diverse sources and ensuring data reliability and accuracy. Ethical Considerations: The use of AI in crisis management raises ethical concerns around privacy, bias, and accountability. Careful consideration is needed to address these issues and ensure the responsible deployment of AI technologies. Limited Resources and Collaboration: Implementing AI-based crisis management systems may be hindered by limited resources, both financial and technological. Effective collaboration between intelligence agencies, emergency responders, and technology providers is crucial to overcome these challenges. Complexity of Crisis Scenarios: Crisis situations can be highly complex, with rapidly evolving dynamics and unpredictable factors. Developing AI models that can accurately predict and respond to such complex scenarios remains a significant challenge. Organizational and Cultural Barriers: Integrating AI into existing crisis management workflows and overcoming organizational resistance to new technologies can be challenging. Effective change management and training are necessary to facilitate the adoption of AI-powered solutions. Regulatory and Governance Frameworks: The governance and regulatory landscape surrounding the use of AI in crisis management is still evolving. Establishing clear guidelines and policies is essential to ensure the responsible and effective deployment of these technologies. It is essential to consider the challenges in using AI for crisis management because addressing these challenges is crucial for the successful implementation and effectiveness of AI technologies in managing crises. By understanding and overcoming these challenges, organizations and governments can maximize the benefits of AI in crisis management. Methodology I these papers the Model - Driven Engineering approach methodology is used for researching the challenges in using AI for crisis management. This methodology involves utilizing Model - Driven Engineering tools, such as metamodels and model transformations, to complement traditional AI approaches and address missing features in AI systems. By applying Model - Driven Engineering, it is possible to extend understanding of unknown situations, particularly in the context of risk and crisis management. This approach allows for a structured analysis of challenges and opportunities in integrating AI technologies into crisis management strategies, providing a comprehensive framework for studying the complexities and limitations of AI in crisis scenarios. Results The results of this research include a comprehensive understanding of the challenges and opportunities in using AI for crisis management. The studies reviewed provide insights into the roles AI can play in crisis management, including enhancing decision-making, optimizing resource allocation, and improving communication during emergencies. Additionally, the research highlights the potential for AI to contribute to crisis management policies, such as finding better treatment routes and supporting policymakers with fast and accurate data. The papers also discuss the challenges and limitations of integrating AI into crisis management strategies, including data availability and quality, ethical considerations, and the need for effective governance frameworks. Furthermore, the research explores the potential for AI to support business operations during crises, such as automating key functions and improving efficiency. Overall, the result of this research provides a detailed analysis of the current state of AI in crisis management, highlighting both the benefits and challenges of its application. This information could be used to inform the development of more effective AI-based crisis management strategies and to address the limitations and challenges associated with AI in this context.